Secondary hypertension - J.A. Ker (South African Family Practice)
Secondary hypertension is rare and the diagnosis may be challenging although, on occasion, there are clinical features indicative of a specific underlying cause. The more commonly encountered causes include renal parenchymal and vascular disease, phaeochromocytoma, endocrine causes, sleep apnoea and drugs.